Does Fusobacterium in Colorectal Cancer Sites Originate From the Oral Cavity? A Pilot Study - Niels Plomp; Kristina Bertl; Marie‐Louise Lydrup; Klas Sjöberg; Hermie J. M. Harmsen; Andreas Stavropoulos (Clinical and Experimental Dental Research)
ABSTRACT Objectives Fusobacterium can contribute to oral diseases, but also pose as a systemic risk factor. This genus, and especially F. nucleatum, can be found in colorectal cancer (CRC) tissue and is involved in multiple aspects of this type of cancer. Previous studies indicated a possible oral origin of these bacteria; however, stronger evidence is needed to reach a definitive conclusion. This pilot study aimed to establish a method to successfully compare, at the strain level, fusobacteria from the oral cavity and CRC resection material for future cohort studies of CRC patients. Material and Methods In a first cohort of eight periodontitis patients, gingival crevicular fluid and saliva were collected. Fusobacterium was isolated on two different media. In a second cohort, saliva and CRC resection material were collected from ten CRC patients. These samples were used for screening of Fusobacterium with culturing, 16S rRNA gene profiling and a PCR‐based approach. Results In the first cohort, different Fusobacterium species were identified in GCF and saliva samples. However, as the total yield of Fusobacterium seemed slightly higher in saliva samples, it was therefore preferred for subsequent sample collection. Thus, in the second cohort, patient‐matched saliva and CRC resection material were screened for Fusobacterium and this showed that nine patients were culture‐positive in the saliva samples; however, no Fusobacterium could be isolated from the resection material. On the other hand, 16S rRNA gene profiling of the resection material indicated that eight CRC patients were positive for Fusobacterium. All eight of these patients carried Fusobacterium in their saliva, indicated by both marker gene PCR and culture‐based screening. Conclusions These pilot results are compatible with data from previous studies, indicating a possible link between oral and CRC‐associated Fusobacterium, and a more in‐depth analysis of specific strains and their characteristics in a larger cohort is justified. Trial Registration The protocol was registered at clinicaltrials.gov (NCT05945082).